Mainstream education as a possible route to recovery and social inclusion: a review - Atkinson, Susan; Collis, Benjamin; Schneider, Justine M. (Emerald, 2018)
To focus on the findings of a review of the Learning Advice Service which provided mainstream learning opportunities and individual support to people using mental health services. The service was decommissioned after 15 years due to service reconfiguration and cost-cutting. Semi-structured Interviews were carried out with members of the Learning Advisor's caseload by a researcher with no affiliation to the NHS or the Institute of Mental Health and no connection to the clients. The researcher also transcribed and analysed the interviews. This ensured there could be no personal or positive bias. The clients faced significant mental health challenges and used the Learning Advice Service to facilitate and support their entry into mainstream learning. The service enabled individuals facing significant mental health challenges to gain access to Adult, Community, Distance and Further and Higher Education facilitated by individual advice, guidance and support. They were able to broaden their sense of identity beyond that of someone using Mental Health Services and to widen their social and educational base. Lack of funding within Mental Health Services to continue this type of work limits research which would further explore the value of mainstream education in the recovery of people with a mental health diagnosis. While this cohort was small because of funding and staffing constraints, it would be possible to generalize to a larger scale, using flexible person-centred ways of working if the will, staffing and funding were made available. Further research is certainly indicated as current practice has moved away from mainstream inclusion to discrete provision with associated limitations. The practical implications include the development of autonomy and the development of a sense of identity that is separate from a mental health diagnosis and where appropriate to gain qualifications and further the student's knowledge. Social implications include broadening one's experience, developing communication skills in a broad context, transferable skills, independence and strengthening one's sense of identity separate from a mental health diagnosis. Individuals from a variety of educational and other backgrounds who expressed an interest in pursuing education in mainstream facilities were encouraged and supported in doing so in flexible and individual ways. It appears to be more usual that people using mental health services are encouraged to learn in groups comprising other people using such services, frequently on mental health service premises with associated limitations.